Coexistence of Cervical Leiomyosarcoma and Gastric-Type Adenocarcinoma In Situ with Extensive Extension to the Endometrium and Fallopian Tube - Ayako Ura; Kanako Ogura; Asumi Sakaguchi; Hiroko Onagi; Daiki Ogishima; Yayoi Sugimori; Kensuke Hamamura; Masaharu Fukunaga; Toshiharu Matsumoto (Case Reports in Pathology)
Cervical leiomyosarcoma is known to be rare from the previous reviews of a large number of malignant cervical tumors. The patient was a 66-year-old woman with irregular vaginal bleeding. She underwent modified radical hysterectomy and bilateral salpingooophorectomy. Histopathologically, we diagnosed the coexistence of uterine cervical leiomyosarcoma and cervical gastric-type adenocarcinoma in situ with endometrial lesions that had continuous and skip patterns and fallopian tubal lesions with a partial lesion. To the best of our knowledge, cases of synchronous leiomyosarcoma and cancers have not often been reported; only two cases of synchronous cervical leiomyosarcoma and cervical squamous cell carcinoma have been published. This case is the first presentation of coincidental primary cervical leiomyosarcoma and cervical gastric-type adenocarcinoma in situ. Additionally, we considered cervical gastric-type adenocarcinoma in situ with continuous lesions on the endometrium and skip lesions on the left fallopian tube.